Exploratory study of multidimensionality elements of small entrepreneurs' network change and development in the southern region of Malaysia - Omar, Siti Sarah; Mohd Aris, Nurul Fadzilla; Yen, Wendy Teoh Ming; Chao, Dorrie; Higgs, Malcolm (2023)
The research aims to empirically explore the multidimensionality elements in small entrepreneurs' network change and development during periods when the entrepreneurs face tipping points. Prior scholars have examined the mix of strong and weak links in small businesses and linked them to business development stages. For small firms to continue experiencing business growth, current literature must emphasize the connection between network strengths and overcoming tipping points. This research explores the multidimensional elements of small entrepreneurs' network change and development that contribute to their survival during the era of tipping points in the Southern Region of Malaysia. This qualitative research uses a multiple case study approach involving eight small firms in the southern region of Malaysia. The data collection methods include analysis of secondary documentation and in-depth interviews with the entrepreneurs using the critical incident interview technique. The data has been analyzed using NVIVO software and has employed Miles and Huberman's (1994) flows of analysis activity. Data triangulation was carried out by interviewing individuals who were seen as having strong or weak ties within the network and who were identified through interviews with the entrepreneurs. The findings enlighten two themes: the entrepreneur-level context and the dyadic-level context. The findings show that the multidimensionality of the individual entrepreneur is demonstrated through their demographic factors, personal values, experience, and capabilities. Therefore, they differ in responding to changes in their networks. Dyadic multidimensionality is found in the tie's content, structure, governance, and the dyadic life cycle. Finally, this research provides theoretical and methodological contributions and offers implications for entrepreneurs, government agencies and policy-makers.